APLIKASI PENJUALAN WAGHE COFFEE BERBASIS WEBSITE MENGGUNAKAN PHP AND MY SQL DENGAN FRAMEWORK BOOTSTRAP - Kuwat Setiyanto; Hafidh Raihan Al Ghifari (Asosiasi Dosen Muda Indonesia, 2023)
Website-Based Waghe Coffee Sales Application. In an era that is all modern like now, technology has a big role in society, people are very dependent on technology and because of that people want services that are easy to access, fast and efficient. The Waghe Coffee Sales Application was built using Visual Studio Code using PHP, MySQL Database and phpMyAdmin, XAMPP and using the Bootstrap Framework, as well as several research methods to get maximum results by means of data collection, application design, implementation and testing. This application has been tested with a blackbox and tested using a computer and mobile with each using 2 different web browsers and 2 different devices and testing the website display. The facilities provided by this application are baskets that assist customers in purchasing goods when purchasing products and there are contacts for customers to contact the admin as well as a payment method by cash on delivery (COD).Â